(Simulation of Wireless Multimedia Sensor Networks (WMSN - Ali, Hanafy M (Arab Journal for Sciences and Research Publishing, 2019)
Wireless multimedia sensor networks (WMSNs) became widely popular because of the availability of low-cost easy-to-use multimedia sensors and devices capable of retrieving and transmitting multimedia content like sound, images and video streams. Simulation of WMSN has followed techniques and tools that are mainly used by similar wireless sensor networks (WSN). This, unfortunately, was not sufficient for the data-intensive nature of WMSN. Therefore, it is still challenging to provide sufficient simulation frameworks for WMSNs. This paper presents a survey of available simulation frameworks and tools for WMSNs. The challenges facing the simulation process are first introduced. Then, the attributes of the ideal WMSN simulation are presented and reviewed. The general model of WMSN simulation environments are also presented and discussed. Finally, a detailed survey of available simulation frameworks and tools are presented. Tools that are inherited from wireless sensor network (WSN) and those made specially for WMSNs are also presented.